Implementation of Physical Distancing Towards Public Services in Palangka Raya City - Irianti Sintaman, Putri (KnE Social Sciences, 2023)
Physical Distancing as an effort to prevent the spread of corona virus (Covid-19) in the City of Palangka Raya, is expected to be carried out by all elements of society, including various fields of public service that are in direct contact with the community. Central and local government directives are obediently implemented. Like the application of keeping the distance in the form of a seat line marked with a yellow line has been arranged in such a way. The purpose of this research is to find out how the application of Physical Distancing to public services in the City of Palangka Raya that affects COVID-19. The results of this study as the direction of e-government based public services to improve service quality during the Covid-19 period. Research methodology uses descriptive qualitative This type of research is a qualitative research method that focuses research by describing the deepest phenomena and digging deep information using sentences or words, where the researcher himself is directly in the field. Based on the results of the study it can be concluded that public services in the City of Palangka Raya continue to run as usual. However, it still implements health protocols and physical distribution in public services. Of the five public services there are those who implement online-based public services and there are also those who perform public services directly by referring to the applicable health protocols in the City of Palangka Raya. Keywords: Implementation; physical distancing; public services